The influence of affective states varying in motivational intensity on cognitive scope - Harmon-Jones, Eddie; Gable, Philip; Price, Tom F. (Frontiers in Integrative Neuroscience, 2012)
We review a program of research that has suggested that affective states high in motivationally intensity (e.g., enthusiasm, disgust) narrow cognitive scope, whereas affective states low in motivationally intensity (e.g., joy, sadness) broaden cognitive scope. Further supporting this interpretation, indices of brain activations, derived from human electroencephalography, suggest that the motivational intensity of the affective state predicts the narrowing of cognitive scope. Finally, research suggests that the relationship between emotive intensity and cognitive scope is bi-directional, such that manipulated changes in cognitive scope influence early brain activations associated with emotive intensity. In the end, the review highlights how emotion can impair and improve certain cognitive processes.